Evaluation of the effect of cell freshness on pyrogen detection using a serum-free monocyte-activation test. - Katsuhiko Hayashi; Mizuki Sano; Toshie Kanayasu-Toyoda; Yuji Morita; Teruhide Yamaguchi; Kenji Ohya; Yutaka Kikuchi; Ken-Ichi Izutsu; Yukiko Hara-Kudo (PLoS ONE)
Pyrogens cause shock symptoms when released into the bloodstream. They are classified into two main categories: endotoxins (lipopolysaccharides [LPS]) and non-endotoxin pyrogens. The monocyte activation test (MAT) is an in vitro assay to detect pyrogens in human monocytes. Cells were incubated in the culture medium, and the cellular response, specifically the production of the inflammatory cytokine interleukin-6 in the culture supernatant, was analyzed using enzyme-linked immunosorbent assay (ELISA). Technical improvements, such as cell acquisition and culture media selection, will be beneficial for the popularization of MAT. The cell freshness was strictly controlled to achieve high MAT sensitivity. However, it is necessary to investigate the usability of older and stored blood samples in the MAT. This study evaluated the effect of cell freshness on MAT using peripheral blood mononuclear cells (PBMCs) isolated from 2- and 5-d-old donated whole blood samples. To mitigate the influence of serum in the culture medium, a serum-free MAT was developed using the LPS-binding protein (LBP) as an enhancer for LPS detection. PBMCs were incubated with a two-fold dilution series of LPS at 0.001-4.096 endotoxin units/mL (EU/mL). Interleukin-6 levels in the culture supernatant were quantified by ELISA in the presence and absence of LBP. In the presence of LBP, the limit of detection (LOD) for LPS was 0.001-0.008 EU/mL. However, in the absence of LBP, the LOD was 0.512 EU/mL. Peripheral PBMCs were 38.6 times more sensitive in the presence of LBP than in its absence. When utilizing the developed serum-free MAT with LBP, 5-d-old PBMCs showed LODs of 0.016-0.064 EU/mL, indicating a 3.1-fold increase in sensitivity compared with 5- to 2-d-old PBMCs. These results suggest that the sensitivity of PBMCs decreased gradually rather than sharply. The study concluded that 2-d-old PBMCs were sufficiently fresh and could be used as serum-free MAT.